2019
DOI: 10.1136/bmjopen-2019-031346
|View full text |Cite
|
Sign up to set email alerts
|

One-year rehospitalisations for congestive heart failure in Portuguese NHS hospitals: a multilevel approach on patterns of use and contributing factors

Abstract: ObjectivesIdentification of rehospitalisations for heart failure and contributing factors flags health policy intervention opportunities designed to deliver care at a most effective and efficient level. Recognising that heart failure is a condition for which timely and appropriate outpatient care can potentially prevent the use of inpatient services, we aimed to determine to what extent comorbidities and material deprivation were predictive of 1 year heart failure specific rehospitalisation.SettingAll Portugue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“… 1 The reasons for readmissions are often related to incomplete decongestion, warranting better implementation of HF care pathways, as well as to other conditions (e.g. DM, chronic obstructive pulmonary disease, and chronic kidney disease), 45 mirroring the high burden of comorbidities in HF. 44 …”
Section: European Epidemiological Data On Heart Failurementioning
confidence: 99%
“… 1 The reasons for readmissions are often related to incomplete decongestion, warranting better implementation of HF care pathways, as well as to other conditions (e.g. DM, chronic obstructive pulmonary disease, and chronic kidney disease), 45 mirroring the high burden of comorbidities in HF. 44 …”
Section: European Epidemiological Data On Heart Failurementioning
confidence: 99%
“… 3 Furthermore, one-fifth of patients admitted for heart failure (HF) are rehospitalised within one year due to a HF exacerbation. 4 The improved survival following a cardiac event results in a growing number of patients living with a heart disease. 5 Therefore, there is need for optimal lifelong secondary prevention.…”
Section: Cardiac Rehabilitationmentioning
confidence: 99%
“…Although the core components and the effectiveness of secondary prevention and CR are well established, rehospitalisation rates for HF and recurrent events for CAD patients remain disappointingly high. 3,4 Important causes are the low uptake of CR and poorer long-term adoption of secondary prevention measures, as shown recently in the EuroAspire audits. 1,11 An array of factors contributes to these low participation rates.…”
mentioning
confidence: 99%
“…1,10,30 Several relevant risk factors for poorer HF prognosis have been reported and those were confirmed in our study. 13,[31][32][33][34][35][36][37][38][39] The MADIT II (Multicenter Automatic Defibrillator Implan tation Trial II) cohort analysis identified re nal failure as one of the strongest predictors of poor prognosis. 35 Gheorghiade et al 36 and Ambrosy et al 37 listed renal failure and low systolic blood pressure among factors influ encing the prognosis of patients hospitalized for HF.…”
Section: Supplementary Materialsmentioning
confidence: 99%